Dynamic-State Adsorption and Elution Behaviour of Uranium(VI) Ions from Seawater by a Fibrous and Porous Adsorbent Containing Amidoxime Chelating Functional Groups - Anyun Zhang; Gunzo Uchiyama; Toshihide Asakura (Adsorption Science & Technology)
To develop an advanced recovery process of uranium from seawater using a macroporous fibrous polymeric material containing amidoxime chelating functional groups (FPAO), the static- and dynamic-state adsorption behaviours of U(VI) ions onto a new type of FPAO were investigated at pH 6.0. It was found that the flow rate and the column specification had a distinct influence on the adsorption of U(VI) ions onto FPAO. When the flow rate was varied from 0.95 ml/min to 3.75 ml/min, the amount of U(VI) ions adsorbed decreased from 379.3 mg/g to 340.6 mg/g while the corresponding equilibrium time diminished from 41.2 h to 10 h. When two types of column of different diameter (Φ) and height (h) were employed, viz. Φ 9.4 mm × h 525 mm and Φ 15.5 mm × h 290 mm, the amounts of U(VI) ions adsorbed and the corresponding equilibrium times were 340.6 mg/g and 10 h and 325.9 mg/g and 13.6 h, respectively, at a constant flow rate of 3.70 ml/min. The use of hydrochloric acid as an eluant for U(VI) ions was also examined by varying its concentration, elution flow rate and the column dimensions. Hydrochloric acid eluted U(VI) ions effectively from the loaded FPAO when employed in the concentration range 0.5–1.0 M. The percentage recovery of U(VI) ions calculated under all elution conditions was greater than 99%.